Desirable Low-Density Lipoprotein Cholesterol Levels for Preventing Stroke Recurrence: A Post Hoc Analysis of the J-STARS Study (Japan Statin Treatment Against Recurrent Stroke). Issue 4 (April 2018) - Hosomi, Naohisa; Kitagawa, Kazuo; Nagai, Yoji; Nakagawa, Yoko; Aoki, Shiro; Nezu, Tomohisa; Kagimura, Tatsuo; Maruyama, Hirofumi; Origasa, Hideki; Minematsu, Kazuo; Uchiyama, Shinichiro; Matsumoto, Masayasu
Abstract : Background and Purpose—: To define desirable target low-density lipoprotein (LDL) cholesterol levels for the prevention of stroke recurrence, a post hoc analysis was performed in the J-STARS study (Japan Statin Treatment Against Recurrent Stroke). Methods—: Subjects (n=1578) were divided into groups based on mean value of postrandomized LDL cholesterol levels until the last observation in 20 mg/dL increments. Adjusted hazard ratios (HRs) and 95% confidence intervals were analyzed for each group, with adjustments for baseline LDL cholesterol, baseline body mass index, hypertension, diabetes mellitus, and statin usage. Results—: The postrandomized LDL cholesterol level until the last observation were 104.1±19.3 mg/dL in the pravastatin group and 126.1±20.6 mg/dL in the control group. The adjusted HRs for stroke and transient ischemic attack and all vascular events decreased in the postrandomized LDL cholesterol level of 80 to 100 mg/dL ( P =0.23 and 0.25 for the trend, respectively). The adjusted HR for atherothrombotic infarction significantly reduced with the usage of statin after adjusting baseline LDL cholesterol levels (HR, 0.39; 95% confidence intervals, 0.19–0.83). The adjusted HR for atherothrombotic infarction and intracranial hemorrhage were similar among the postrandomized LDL-cholesterol–level subgroups ( P =0.50 and 0.37 for the trend, respectively). The adjusted HR for lacunar infarction decreased in the postrandomized LDL cholesterol level of 100 to 120 mg/dL (HR, 0.45; 95% confidence intervals, 0.20–0.99; P =0.41 for the trend). Conclusions—: The composite risk of stroke and transient ischemic attack reduced in the postrandomized LDL cholesterol level of 80 to 100 mg/dL after adjusting for statin usage. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00221104. Abstract : Supplemental Digital Content is available in the text.